Perceptions and Reactions of Host Communities of the Niger Delta University Towards Industrial Actions in Nigeria - Michael-Olomu, Oyintonyo; Imbazi, Woyengitari (Social Science Research, 2022)
Industrial actions have been noted to affect its environments. Despite this, several studies have focused exclusively on industrial actions and their impacts on employees and productivity, while neglecting the reactions of the host communities which are very important stakeholders. This study, therefore, examined the perceptions and reactions of host communities towards industrial actions to universities industrial actions using the Niger Delta University (NDU) as a case study. This cross-sectional was conducted among 418 respondents in two host communities of the Niger Delta University (Amassoma and Ogobiri), using simple random sampling to administer a structured questionnaire. Quantitative data were analysed using univariate, bivariate and multivariate statistics at p≤0.05. Results show that the average age of the respondents was 38.5 years. Results indicated that the Academic Staff Union of Universities (ASUU) was the main union in NDU that embarked on industrial actions. Also, socio-demographic variables were found to have a predictive influence on the perceptions about industrial actions. For instance, females were 38.8% less likely to feel uncomfortable with industrial actions than their male counterparts. Still, those who were in the age group between 30 and 39 years were found to be (OR = 0.340, p<0.05) less likely to feel uncomfortable with NDU industrial action than those who were less than 20 years. Additional, protests, roadblocks, and demonstrations were some of the means of reactions against industrial action used by host communities. The study recommended that stakeholders in university should curb the early warning signs of industrial actions bearing in mind that the effects go beyond the institution.